Immigration Enforcement and Infant Health - Catalina Amuedo-Dorantes; Brandyn F. Churchill; Yang Song (Institute of Labor Economics (IZA), 2020)
The past two decades have been characterized by an unprecedented increase in interior immigration enforcement and heightened stress due to fears of family separation and loss of income among undocumented immigrants. Using vital statistics on infant births from the National Center of Health Statistics for the 2003 through 2016 period and a difference-in-differences design, we compare the health outcomes of infants with likely undocumented mothers before and after the intensification of immigration enforcement within U.S. counties. We find that intensified enforcement, especially during the third trimester, increases the likelihood of low birth weight (<2500 grams). We also present suggestive evidence that the effect could be driven by heightened stress and fears associated to police-based enforcement during pregnancy. The findings underscore the importance of current immigration policies in shaping the birth outcomes of many American children.
Keywords: I10; I12; K37; 330; immigration enforcement; undocumented immigrants; infant health